PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP ATTITUDE TOWARD USING PADA OJEK ONLINE UBER - Yunika Komalasari; Marjito Marjito (Jurnal Computech & Bisnis (e-Journal), 2019)
Transportation is a service provided to help goods or people to be taken from one place to another, the presence of online transportation applications that can be easily installed on a smartphone. The presence of online application-based transportation services that use the internet is very influential for the community in all activities quickly and efficiently. The purpose of this study is to determine the level of acceptance of uber application technology as an online transportation media, where this study is to find out and explain the influence of perceived ease of use on the Uber application. From the results of path analysis it can be concluded that: the perception of ease of use (Perceived Ease of Use) variable has a significant positive effect on attitude (Attitude Toward Using), the perception of the usefulness variable (Perceived Usefulness) has a significant positive effect on attitude (Attitude Toward Using), the perception of ease of use (Perceived Usefulness) and the perception of the usefulness of use (Perceived Usefulness) has a significant positive effect on attitude of use (Attitude Toward Using) with a value of t count of 5.371 in sig. t amounting to 0,000Keywords: Perception of Ease of Use, Perception of Use, Attitude of UseDOI : http://doi.org/10.5281/zenodo.3625290